Pembinaan Gadis-Gadis Penghibur - Uras Siahaan; Agustina Evelin Tambunan (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2020)
Abstract: This paper is based on the experience of nurturing and educating from a social worker at the Berdikari Foundation (pseudonym) in South Jakarta, in collaboration with the Manunggal Foundation (pseudonym), to educate abandoned children, who plunge into the Night world, as aneffortto "Reduce" these children. The Children collected and accommodated at the Berdikari Foundation are mainly girls from the ages of 17 to 24 years old and not married, nor have children. They are coming from Jakarta and the surrounding area. These girls are trained to live a disciplined life, educated ethically and to get regular junior and high school diplomas through education Package B and C. These children are accommodated and educated for a maximum of 1 year and a minimum of 6 months. During this education, contact with relatives and friends outside the shelter is limited, to the extent that is important and given the rules that they must obey. If they cannot obey it, these children will be returned to their parents. Thus, the gathering of these children must be acknowledged and approved by their respective parents. Thus, the data and finding sobtained are based on direct sources in the field. Hope from this Foundation, these children after the training period can come back in to the community with more confidence and equipped with adequate knowledge and skills. The Foundation's good relations with other parties and donors are the main stay to look for jobs that match the children's talents. The finding sobtained in the field that there is still a large number of failures, i.e. around 40% of young girls will return to prefer a free life and not expectfor a normal life, as expected by the Foundation and donors who contribute their energy and thoughts for this project. Therefore, other efforts also need to be considered in addition to educating them is the approach to the families of these "patients", so that they not only try to be free from the burden of responsibility for coaching their children, but also hope for a decent life and future for them. Keywords: Girls, Fostering and Education